INTEGRATED WATER RESOURCES MANAGEMENT IN THE REPUBLIC OF KAZAKHSTAN: PROBLEMS AND PROSPECTS (Journal of Geography and Environmental Management, 2018)
The article analyzes the state of Kazakhstan’s water resources, shows that in recent years the flow of Trans Boundary Rivers has been decreasing. As a result, in the coming years, with the growth of thecountry’s economic potential, based on the development of rich mineral resources, fuel, energy and land resources, there will be a serious problem with water supply. The scarcity and irrational use of freshwater resources pose a serious threat to the sustainable development and protection of the country’s environment. The regulation of water use is of great importance in solving this problem. It is  necessary to ensure the implementation of the Program for the rational use and protection of water resources in the context of large river basins by introducing new technologies for water supply and sanitation. The system of integrated water resources management should become the basis of the country’s interstate and interstate water management policy. At present, the countries of Central Asia are moving towards the introduction of the principles of sustainable development into strategic documents and public administration practices. Integrated water resources management is one of the tools for the transition to sustainable development. This article is a review of progress made in the planning and implementation of integrated water resources management. The article summarizes the problems, successes, and directions for further integration in the field of water resources management. It also examines the successes and enormous difficulties still facing the regions, in particular, the issues of trans boundary waters, where states have different views and priorities for water use.